Branding Down to the Core: Branding Not-For-Profits - Patricia Tan (Healthcare Quarterly, 2003)
… the brand is the platform on which the motivation behind the organization's work may be articulated, and the significance of its work may be appreciated. Many not-for-profits do not view their organization as a brand. After all, the reason for being lies in the purpose. Branding is something corporate businesses do to justify their existence. But what is an organization's purpose? And what if everyone in the organization does not agree on that purpose over time or across departments? How can an organization formalize a strategy if it isn't sure what the mission is?